Can We Trust the Math? Correlation of Objective Postvoid Residual With Calculated Subtraction Postvoid Residual. Issue 1 (21st April 2021) - Jansen, Sierra M.; Woll, Abbi; Brown, Heidi W.; Swift, Steven; Edenfield, Autumn; Zhou, Qianqian; Heisler, Christine A.
Abstract : Objective: The aim of the study was to determine the accuracy of postvoid residual (PVR) by subtraction as compared with objective measurement by bladder scan or catheterization. Methods: This is a secondary analysis of postoperative patients who underwent avoiding trial by retrograde bladder instillation. Fill volume, spontaneous voided volume, and PVR were objectively measured; PVR was also calculated. Pearson correlation compared PVR by subtraction versus objective measurement. We then defined postoperative urinary retention (POUR) at 3 different PVR values (100 mL, 150 mL, and 200 mL) to compare the sensitivity, specificity, and positive and negative predictive values of subtraction for detecting urinary retention at these 3 thresholds. Results: Data were available for 155 patients after urogynecologic surgery. Median PVR by objective measurement was 46 mL (interquartile range = 11–146 mL). Median calculated PVR by subtraction was 10 mL (interquartile range = 0–100 mL). Objective measure and subtraction PVR values were strongly correlated (Pearson coefficient = 0.78, P < 0.001). Using a threshold of 200 mL to define POUR resulted in the highest negative predictive value and the lowest absolute number of both false negatives and false positives. Even using this threshold, 11 (48%) of 23 women with POUR by measurement were misclassified as not having POUR when ascertained by subtraction. Conclusions: Although subtraction PVR correlates well with objective PVR measurement, almost half of women with a PVR volume of greater than 200 mL by objective measurement are miscategorized as voiding normally by subtraction PVR. Based on these findings, reliance on objective PVR measurement in postoperative patients is preferable to subtraction PVR.